1995
DOI: 10.1172/jci117891
|View full text |Cite
|
Sign up to set email alerts
|

Altered representation of naive and memory CD8 T cell subsets in HIV-infected children.

Abstract: CD8 T cells are divided into naive and memory subsets according to both function and phenotype. In HIlV-negative children, the naive subset is present at high frequencies, whereas memory cells are virtually absent. Previous studies have shown that the overall number of CD8 T cells does not decrease in HIV-infected children. In studies here, we use multiparameter flow cytometry to distinguish naive from memory CD8 T cells based on expression of CD11a, CD45RA, and CD62L. With this methodology, we show that withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 27 publications
2
89
0
Order By: Relevance
“…These findings support the view that the levels of WRN, BLM and RecQL1 helicases are crucial to guarantee genomic stability in actively proliferating and/or transformed cells [11]. Multiple experimental evidences suggested analogies of T cell dynamics between advanced ageing and HIV infection [19][20][21][22][23][24][25][26][27][28][29][30]. Recently, it has been suggested that through a process of continuous immune activation HIV-1 infection leads to an acceleration in the ageing process of the adaptive immune system, thus contributing to immunodeficiency [31].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings support the view that the levels of WRN, BLM and RecQL1 helicases are crucial to guarantee genomic stability in actively proliferating and/or transformed cells [11]. Multiple experimental evidences suggested analogies of T cell dynamics between advanced ageing and HIV infection [19][20][21][22][23][24][25][26][27][28][29][30]. Recently, it has been suggested that through a process of continuous immune activation HIV-1 infection leads to an acceleration in the ageing process of the adaptive immune system, thus contributing to immunodeficiency [31].…”
Section: Discussionsupporting
confidence: 77%
“…+ subset [19][20][21][22][23] expansion of CD8 + CD28 -T cells [24], as well as the restriction of the CD8 + T cell repertoire [25,26] suggest a typical perturbation of the T cell subpopulations that is seen in both HIV disease and advanced ageing. Moreover, a decreasing number of recent thymic emigrants, identified as T cell receptor excision circles (TRECs) [27][28][29], have been observed with ageing and in HIVinfected individuals, while highly active antiretroviral therapy (HAART) treatment leads to an increased thymic output [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of MIP-1␤ by naive and memory subsets was investigated by using CD45R0 and CD62L to define naive (CD45R0 Ϫ CD62L ϩ ), M1 (CD45R0 ϩ CD62L Ϫ ), M2 (CD45R0 ϩ CD62L ϩ ), and M3 (CD45R0 Ϫ CD62L Ϫ ) subsets similar to those described by Roederer and coworkers (36,37) (Fig. 6a).…”
Section: Synthesis Of Mip-1␤ By Cd8 ؉ Memory Subsets Defined By Cd45rmentioning
confidence: 81%
“…Loss of CD4 þ T cells is known to be the hallmark of HIV infection and it is a well accepted laboratory marker of HIV disease progression [6,7]. Also, changes in other T cell subsets have been implicated in HIV þ persons from studies in Europe and North America: expansion of CD8 þ T cells [8], loss of naive CD8 þ T cells, increase of both CD4 þ and CD8 þ T cell memory subsets [9,10] and increased activated CD4 þ and CD8 þ T cell subsets [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%